Distributed economic dispatch for smart grid system based on Nesterov gradient method - Zhao, Chen (2016)
Economic dispatch (ED) is considered as one of well-studied and key problems in the power system research. For solving ED problems normally we have centralized methods (CM) and distributed methods (DM) that can obtain the optimal solution. CM and DM have their own advantages and disadvantages, whereas the future treads will focus more on distributed methods. By decomposing centralized optimization into optimizations at local agents, an algorithm is developed for each agent to iteratively estimate a solution of the optimization problem in a distributed manner with limited communication among neighbors. In this report, it will present several methods especially a distributed economic dispatch strategy based on Nesterov gradient method for the smart grid systems. With the supports of appropriate mathematics functions and algorithms, this new distributed method will be more flexible and give a faster response, which helps the power system dispatching process more economical, efficient and effective.